GENDER MAINSTREAMING IN THE CONTEXT OF ACEH DEVELOPMENT - Gunawan Adnan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2017)
Gender mainstreaming is a globally accepted strategy for promoting gender equality. Mainstreaming is not an end in itself but a strategy, an approach, a means to achieve the goal of gender equality. Mainstreaming involves ensuring that gender perspectives and attention to the goal of gender equality are central to all activities - policy development, research, advocacy/dialogue, legislation, resource allocation, and planning, implementation and monitoring of programs and projects. Gender mainstreaming is, therefore, becoming a collective awareness and concern in most countries since it is viewed as one of the most appropriate, comprehensive and representative approaches to solve both the problem of gender inequality and the problem of violence against women and children including in Indonesia in general and Aceh in particular. This study is aimed at exploring how gender mainstreaming initiatives, attempts to integrate a gender equality approach to post-tsunami and post-conflict reconstruction and development efforts in Aceh, take part in the social and political reconstruction by both reproducing and subverting gendered images of temporality and spatiality as well as promoting a holistic gender equality in all aspects of life. The method used in doing this research is a library method in which all related data and library resources are collected, examined and finally analyzed. The result of this study suggests, among others, that gender mainstreaming should be based on a holistic approach, not only in spirit and conceptual basis but also in practical and social reality basis, such as empowering women in having equal access toward education, access to economic resources, access to the right of possessing property, etc. Moreover, one of another important result of this study is that the violence against women and children that still commonly occur almost everywhere in the world should be viewed as collective enemy and challenge which needs to be faced and eliminated collectively as well.